Prevalence of sarcopenia in inpatients 70 years and older using different diagnostic criteria. Issue 2 (28th November 2018) - Reijnierse, Esmee M.; Buljan, Angela; Tuttle, Camilla S. L.; van Ancum, Jeanine; Verlaan, Sjors; Meskers, Carel G. M.; Maier, Andrea B.
Abstract: Aim: To compare prevalence rates of sarcopenia applying multiple diagnostic criteria in hospitalized older patients. Design: Observational, longitudinal EMPOWER study. Methods: A total of 378 hospitalized inpatients aged 70 years and older were recruited. Muscle mass and strength were measured using bioelectrical impedance analysis and handheld dynamometer respectively. Nine commonly used diagnostic criteria for sarcopenia were applied. Analyses were stratified for sex. Results: Mean age was 79.7 years ( SD 6.43) and 50.8% were males. Depending on the applied criterion, prevalence of sarcopenia ranged between 12.0–75.9% in males and 3.1–75.3% in females. Males had a higher prevalence of sarcopenia compared with females in all but one of the applied diagnostic criteria. In males, highest prevalence of sarcopenia was found using muscle mass as diagnostic criterion while in females this was observed when using muscle strength. Five male and one female hospitalized older patients were sarcopenic according to all applied diagnostic criteria.